Family Instability as a Predictor of Academic Performance Among Secondary School Students in Oshodi/Isolo Local Government Area of Lagos State, Nigeria - Alabi, M. A.; Jimoh, , J. A; Biwai, , Y.; Lasisi, , A. K. (Kashere Journal of Education, 2021)
The research investigated Family instability as a predictor of academic achievement of secondary school students. survey research design of expo-facto type was used for the study. A total of 200 participants were randomly sampled for the study. Data were collected with self-developed family instability questionnaire, while the students’ scores in mathematics and English were used as academic achievement data. The reliability of the instrument was measured through pilot testing and Cronbach’s alpha test was employed to check the consistency and accuracy of the measurement scale. A reliability coefficient of 0.73 was obtained, which indicates that the items in the instrument measured similar concept. Three hypotheses were raised and tested at 0.05 level of significance. The data were analysed using Pearson product moment statistics method. The result of the analysis showed a significant relationship between family instability and academic achievement of secondary school students (junior, senior). On the basis of the findings it was recommended among others that that couples should avail themselves of the services of marriage counselors in the resolution of marital disputes.